2018
DOI: 10.3390/vaccines6030038
|View full text |Cite
|
Sign up to set email alerts
|

The Immunity Gap Challenge: Protection against a Recent Florida Clade 2 Equine Influenza Strain

Abstract: Vaccination is one of the most effective tools for limiting the impact of equine influenza (EI). The humoral immunity established following a primary vaccination course can decrease significantly between the second (V2) and third immunisations (V3), leaving some horses insufficiently protected for several weeks. This so-called “immunity gap” poses a challenge to all EI vaccines. During this period, the EI infection of vaccinated animals may be followed by marked clinical signs and virus shedding. However, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
2
9
0
3
Order By: Relevance
“…A possible hypothesis is that horses born in 2016 and 2017 were sampled during their primary course of EI vaccination and may have not yet developed a complete and robust EI humoral immune response at the time of sampling. The results are correlated with a previous field study that highlighted a large frequency of Thoroughbred foals displaying low or negative SRH antibody titers during their primary EI immunization and up to 5 months after the third EI immunization (V3) [27] and other clinical studies highlighting the immunity gap frequently observed in the weeks preceding the third EI immunization [28][29][30]. In the field study, the frequency of seronegative foals (i.e., SRH = 0 mm 2 ) was greater than 25% at different sampling time points during the primary EI immunization (at the time of first immunization, two weeks and three months after the second immunization and two days after the third immunization) [27].…”
Section: Discussionsupporting
confidence: 87%
“…A possible hypothesis is that horses born in 2016 and 2017 were sampled during their primary course of EI vaccination and may have not yet developed a complete and robust EI humoral immune response at the time of sampling. The results are correlated with a previous field study that highlighted a large frequency of Thoroughbred foals displaying low or negative SRH antibody titers during their primary EI immunization and up to 5 months after the third EI immunization (V3) [27] and other clinical studies highlighting the immunity gap frequently observed in the weeks preceding the third EI immunization [28][29][30]. In the field study, the frequency of seronegative foals (i.e., SRH = 0 mm 2 ) was greater than 25% at different sampling time points during the primary EI immunization (at the time of first immunization, two weeks and three months after the second immunization and two days after the third immunization) [27].…”
Section: Discussionsupporting
confidence: 87%
“…The SRH antibody levels measured in weanlings with Equilis ® Prequenza-Te were similar to the antibody response measured in ponies vaccinated with the same EI vaccine in a recent study conducted by Paillot et al (2018) [37]. Significant clinical and virological protections were measured when these ponies were experimentally infected with a recent FC2 EIV strain, five months after V2 [37].…”
Section: Discussionsupporting
confidence: 78%
“…The other two EI vaccines (Equilis ® Prequenza-TE and Calvenza-03 ® ) contain H3N8 heterologous strains. The cross protection between EIV strains is well documented, as recently demonstrated by Paillot et al (2018) [37]. Gildea et al (2011) [25] found that the humoral antibody response was similar for all vaccines used and, for all antigens tested [25], sera from vaccinated horses were cross-reactive [38].…”
Section: Discussionmentioning
confidence: 88%
“…Closing the immunity gap is a concern, because this is the age in which performance horses from different stables are comingled for training, presenting elevated risk of disease exposure. Different vaccines and vaccination schedules have shown mixed success [ 109 , 110 , 111 ]. Maternal antibody interference with foal EIV vaccinations is a concern, especially with inactivated virus vaccines [ 110 , 112 , 113 , 114 , 115 ], such that the recommended age for the first (priming) dose is typically 6 months in foals whose dams are expected to be EI-seropositive.…”
Section: Inactivated Whole Virus Ei Vaccinesmentioning
confidence: 99%
“…Different vaccines and vaccination schedules have shown mixed success [ 109 , 110 , 111 ]. Maternal antibody interference with foal EIV vaccinations is a concern, especially with inactivated virus vaccines [ 110 , 112 , 113 , 114 , 115 ], such that the recommended age for the first (priming) dose is typically 6 months in foals whose dams are expected to be EI-seropositive. Fortunately, in such foals, maternal antibodies from colostrum are protective, and EI is seldom a problem until after 6 months of age.…”
Section: Inactivated Whole Virus Ei Vaccinesmentioning
confidence: 99%